Atención al cliente en el Servicio de Hospedaje “Los Andes” de la ciudad de Babahoyo - Pulecio Rivadeneira, Mervin Adrian (2020)
The present case study mentions the problems that are developed in the "Los Andes" lodging service located in the Babahoyo canton, by applying the descriptive methodology to detail various situations that arise within the company, it is mentioned that inadequate equipment and its age has made the lodging experience not pleasant. Therefore, it is recommended that for there to be an experience, it has been pleasant for users to have equipment and special attention for them to return, the hosting service has been recommended in a positive way by users, in turn, empowerment. that the collaborators must have to be able to give a solution to the problems that may exist on the part of the guests is very indispensable, complementary services such as the internet and the private parking service.